Determinan Kepatuhan Wajib Pajak UMKM: Studi KPP Pratama Ponorogo - Andriyani, Lisa; Mustoffa, Ardyan Firdausi; Ardiana, Titin Eka (Universitas Muhammadiyah Semarang, 2022)
This study aims to determine the effect of the implementation, level of understanding of Government Regulation no. 23 of 2018, tax sanctions, and tax socialization on MSME Taxpayer Compliance Registered at KPP Pratama Ponorogo. MSMEs play a significant role in economic growth in Indonesia, so MSMEs are the most significant tax contributor in the economy compared to large companies. The most significant tax revenue comes from the MSME sector because the growth of MSMEs increases yearly. The population in this study is 38.387 taxpayers registered at KPP Pratama Ponorogo in 2021. Determination of the sample using the Slovin formula with the sampling technique using snowball sampling.“The number of samples in this study was 99 MSME taxpayers registered at KPP Pratama Ponorogo.“This type of quantitative research with primary data originating from the distribution of questionnaires. All data collected in this study were analyzed using multiple linear regression analysis models with the SPSS program.”The stages of testing in this research include descriptive statistical analysis, data quality test, classical assumption test, multiple linear regression analysis, and hypothesis testing. The results showed that: (1) the application of PP no. 23 of 2018 has a positive and significant effect on MSME taxpayer compliance. (2) the level of understanding of PP No. 23 of 2018 has a positive and significant effect on MSME taxpayer compliance. (3) tax sanctions positively and significantly affect MSME taxpayer compliance. (4) tax socialization positively and significantly affects MSME taxpayer compliance. (5) Simultaneously, the application of PP No. 23 of 2018, the level of understanding of PP No. 23 of 2018, tax sanctions and tax socialization significantly affect MSME taxpayer compliance.